Super-resolution Photoacoustic Microscopy Using Near-field Localization by a Plasmonic Metal Nanoaperture: A Simulation Study - Park, Byullee (2018)
Super-resolution microscopy (SRM) is becoming increasingly important to study nanoscale biological structures. Two most widely used devices for SRM are super-resolution fluorescence microscopy (SRFM) and electron microscopy (EM). For biological living samples, however, SRFM is not preferred since it requires exogenous agents and EM is not preferred since vacuum is required for sample preparation. To overcome these limitations of EM and SFRM, we present a simulation study of super-resolution photoacoustic microscopy (SR-PAM). To break the diffraction limit of light, we investigated a sub-10 nm near-field localization by focusing femtosecond laser pulses under the plasmonic nanoaperture. Using this near-field localization as a light source, we numerically studied the feasibility of the SR-PAM with a k-Wave simulation toolbox in MATLAB. In this photoacoustic simulation, we successfully confirmed that the SR-PAM could be a potential method to resolve and image nanoscale structures.